Die Konstituentenstruktur der adjektivischen Komposita im Deutschen und Polnischen - Mikołajczak, Sławomir (Studia Germanica Posnaniensia, 2018)
The subject of the article is the analysis and confrontation of adjectival compounds in German and Polish according to CS-rules. The goal of the analysis and confrontation is the classification of adjectival compounds in both languages and conclusions as for their differences, similarities and productivity.